2022
DOI: 10.3390/su141811196
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Perceptions of Food Waste in the UAE

Abstract: This study examines the relationship between food waste and gender, income, and where students live. The research aligns with the United Nations Sustainable Development Goals 2, 11, and 12; moreover, the massive global food shortage in 2022 due to the conflict between Russia and Ukraine makes saving food a priority. A questionnaire was used to collect data from 201 students at the United Arab Emirates University (UAEU). A large proportion of the respondents were female (71.6%). The most common reasons cited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(60 reference statements)
1
8
0
Order By: Relevance
“…From the results shown in Table 1, we can see that 52% of the respondents were of the opinion that the largest amount of food waste is generated when eating out, with the second largest amount of food waste being consumed in the household. These results are consistent with a similar survey (Yagoub et al, 2022) conducted among UAE students, which found that 38% of respondents believed that a large proportion of food is wasted at the consumption level. Based on this data, it should be noted that efforts should be directed towards educational campaigns to reduce food waste at the consumption stage.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…From the results shown in Table 1, we can see that 52% of the respondents were of the opinion that the largest amount of food waste is generated when eating out, with the second largest amount of food waste being consumed in the household. These results are consistent with a similar survey (Yagoub et al, 2022) conducted among UAE students, which found that 38% of respondents believed that a large proportion of food is wasted at the consumption level. Based on this data, it should be noted that efforts should be directed towards educational campaigns to reduce food waste at the consumption stage.…”
Section: Resultssupporting
confidence: 92%
“…Understanding the root causes of food waste among students requires a multidimensional approach. Research in this area considers factors such as individual attitudes, knowledge, and awareness of food waste (Yagoub et al, 2022); social norms and peer influence (Stefan, Herpen, Tudoran, and Lähteenmäki, 2013); campus dining practices; and the presence of initiatives to reduce food waste (Smith, 2015). By gaining insight into these factors, interventions can be developed to effectively target student behaviour and promote more sustainable consumption patterns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Food waste negatively affects the environment and the agriculture industry [ 9 ]. The United Arab Emirates (UAE) spends around USD 4 billion annually (equivalent to AED 14.69 billion), making up around 40% of the daily domestic waste in the UAE [ 7 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies report that the young generation throws away food more than adults and parents (Bravi et al, 2019(Bravi et al, , 2020Ellison et al, 2019;Yagoub et al, 2022). Shifts in urban lifestyles to become more urban encourage the young generation not to cook food for themselves but not to be able to utilize leftover food, which can increase food waste (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in urban lifestyles to become more urban encourage the young generation not to cook food for themselves but not to be able to utilize leftover food, which can increase food waste (Zhang et al, 2020). Understanding the behavior of the young generation in Indonesia is of utmost importance, given that the young generation has a large percentage of the total population of Indonesia (24.34 %) (Statistics Indonesia [BPS], 2022b) and generates more waste than adults (Ellison et al, 2019;Yagoub et al, 2022). Therefore, engagement and awareness in the reduction can have a significant impact on reducing food waste.…”
Section: Introductionmentioning
confidence: 99%